2017
DOI: 10.1590/s1677-5538.ibju.2016.0244
|View full text |Cite
|
Sign up to set email alerts
|

Artificial urinary sphincter for urinary incontinence after radical prostatectomy: a historical cohort from 2004 to 2015

Abstract: This study aimed to retrospectively evaluate a cohort of patients with prostate cancer and persistent urinary incontinence after radical prostatectomy. From January 2004 to December 2015, eighty-six individuals were identified to have received an AUS implant, provided by a private nonprofit HMO operating in Belo Horizonte, Brazil. On total, there were 91 AUS implants, with a median interval between radical prostatectomy and AUS implant of 3.6 years (IQR 1.9 to 5.5). The rate of AUS cumulative survival, after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Postoperative incontinence is still a common problem following surgery for prostate cancer, even we used newer techniques such as robotic-assisted laparoscopic prostatectomy (RALP). It was reported that the incidence rate of UI reaches 8-87% on the sixth month and 5-44.5% on the twelfth month postoperatively [2][3][4][5]. Recently, a prospective, controlled [3], non-RCT of patients undergoing RP in 14 centers using RALP or radical retropubic prostatectomy (RRP) was published.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative incontinence is still a common problem following surgery for prostate cancer, even we used newer techniques such as robotic-assisted laparoscopic prostatectomy (RALP). It was reported that the incidence rate of UI reaches 8-87% on the sixth month and 5-44.5% on the twelfth month postoperatively [2][3][4][5]. Recently, a prospective, controlled [3], non-RCT of patients undergoing RP in 14 centers using RALP or radical retropubic prostatectomy (RRP) was published.…”
Section: Discussionmentioning
confidence: 99%
“…All these treatments may benefit patients; Although, it cannot be denied that the selective serotonin reuptake inhibitor drugs such as duloxetine, which is often accompanied by symptoms of insomnia, nausea, loss of appetite, irritability, and other side effects [ 11 , 17 ]. Further, surgical interventions are traumatic forms of treatment and are also costly [ 18 ]. Pelvic floor muscle training is the most used conservative treatment for urinary incontinence, but for elderly male patients with prostate cancer, whether functional training is carried out correctly is difficult to evaluate and assess, and it is challenging to implement.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, incidence of postoperative urinary incontinence cannot be ignored. Although the occurrence of urinary control disorder after radical prostatectomy differs among countries and studies [ 7 , 8 ], overall incidence of this postoperative complication is higher than other side effects [ 8 ]. When postoperative urinary incontinence occurs, patients frequently develop psychological problems, including decreased self-esteem, irritability, and fear, which severely impair their quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%